Fabrication of New (Ba0.97Ca0.03)(Zr0.94Sn0.06)O3 Ceramics by the Combustion Technique. Issue 1 (26th January 2016) - Mathrmool, Krailas; Vittayakorn, Naratip; Bongkarn, Theerachai
Abstract : In this study, new (Ba0.97 Ca0.03 )(Zr0.94 Sn0.06 )O3 BCZS ceramics were synthesized by the combustion technique using glycine as fuel. The powders and ceramics were calcined from 1, 000 to 1, 200 °C for 2 h and sintered from 1, 500 to 1, 675 °C for 2 h. A pure perovskite phase was found in the powder calcined at higher than 1, 150 °C and the purity phase of the ceramics was detected in all samples. The average particle size and grain size increased approximately from 73 to 103 nm and from 0.51–1.61µm when firing temperatures increased. The calcined powders exhibited tight agglomerates at low calcination temperatures and they changed to loosely bound agglomerates at higher calcination temperatures. The densest ceramics were discovered in the samples sintered at 1, 650 °C. The dielectric constant (ϵr ) and loss factor (tan δ) values measured at 100 kHz of this sample were found to be 44 and 0.01, respectively at room temperature.